2015
DOI: 10.1016/j.pathophys.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of primary and persistent cytomegalovirus infection on the progression of acute colitis in a murine model

Abstract: Cytomegalovirus (CMV) infects 60-100% of the population worldwide. CMV has been implicated in many diseases through the induction of inflammation. Inflammatory bowel disease (IBD) affects over 1 million Americans annually. IBD, in particular ulcerative colitis, has been associated with CMV infection. Here we use a murine model to test if both primary and persistent CMV infections exacerbate colitis. C57Bl/6J mice were injected with mock inoculum or murine CMV (mCMV) 4d (primary infection) or 6wks (persistent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies in immunocompromised NHP animal models and immunocompromised people with UC and CD demonstrate that intestinal inflammation and injury can be both induced [ 289 ] and exacerbated [ 24 , 290 , 291 ] following exposure to viral pathogens. Mouse models have also been used to facilitate acute colitis using cytomegalovirus to exacerbate DSS-induced colitis [ 292 ]. From the information described, it appears that a causal association between viral infections and the induction of intestinal inflammation in immunocompetent individuals remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in immunocompromised NHP animal models and immunocompromised people with UC and CD demonstrate that intestinal inflammation and injury can be both induced [ 289 ] and exacerbated [ 24 , 290 , 291 ] following exposure to viral pathogens. Mouse models have also been used to facilitate acute colitis using cytomegalovirus to exacerbate DSS-induced colitis [ 292 ]. From the information described, it appears that a causal association between viral infections and the induction of intestinal inflammation in immunocompetent individuals remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we observed HCMV-positive intestinal epithelial cells in an IBD patient associated with HCMV, but the existence of a correlation/association does not necessarily indicate causality. Nevertheless, CMV infection experiments in mouse models of IBD have shown that acute and latent CMV infection exacerbates intestinal inflammation [35][36][37][38]. Although the underlying mechanism are not entirely understood, it was demonstrated that concomitant MCMV infection increased gross bleeding [35], induced the production of pro-inflammatory cytokines or chemokine ligands in the colon [36,38], or stimulated gut immune responses to the gut microbiota [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed HCMV positive intestinal epithelial cells in an IBD patient associated with HCMV, but the existence of a correlation/association does not necessarily inidcate causality. Nevertheless, CMV infection experiments in mouse models of IBD have shown that acute and latent CMV infection exacerbates intestinal inflammation [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism are not entirely understood, it was demonstrated that concomitant MCMC infection increased gross bleeding [34], induced the production of proinflammatory cytokines or chemokine ligands in the colon [35,37], or stimulated gut immune responses to the gut microbiota [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation